2009
DOI: 10.1108/17410380910953739
|View full text |Cite
|
Sign up to set email alerts
|

Using data envelopment analysis (DEA) to evaluate the operational performance of the wafer fabrication industry in Taiwan

Abstract: PurposeThe purpose of this paper is to use data envelopment analysis (DEA) to evaluate the efficiency of the wafer fabrication industry in Taiwan.Design/methodology/approachThe input variables are total assets, operation costs, and operation expenditures, and the output variable is net sales. This study uses the Pearson correlation to indicate positively correlation between input and output variables, applies DEA to analyze the efficiency scores, and utilizes Mann‐Whitney U‐test to compare the efficiency score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
1
4
0
1
Order By: Relevance
“…This study analyzed the correlation between inputs and the outputs variables from 2007 to 2009. The results in Table IV showed that the Pearson correlation between the inputs and outputs variables are positive and the requirements of isotonicity condition is satisfied for the DEA analysis (Chen and Chen, 2009). This study used DEA methodology to calculate the technical efficiency of the targeted banks.…”
Section: Analysis Of Resultsmentioning
confidence: 94%
“…This study analyzed the correlation between inputs and the outputs variables from 2007 to 2009. The results in Table IV showed that the Pearson correlation between the inputs and outputs variables are positive and the requirements of isotonicity condition is satisfied for the DEA analysis (Chen and Chen, 2009). This study used DEA methodology to calculate the technical efficiency of the targeted banks.…”
Section: Analysis Of Resultsmentioning
confidence: 94%
“…They used AHP to collect non-quantitative data relative to quality and flexibility, while implemented DEA to identify inefficient layout designs. Chen and Chen (2009) employed DEA to evaluate performance of wafer fabrication companies in Taiwan and the Malmquist productivity index to measure efficiency over several periods of time. Al-Refaie (2009) adopted DEA to compare efficiencies of different techniques used in the surface-mount-technology industry to optimize manufacturing processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…DEA can identify units that are inefficient and can quantify the amount of the improvement to achieve the efficiency frontier. Research on the measurement of efficiency, especially with the approach of DEA has been done in various fields, such as the measurement of SME [38], [39], public sector [40], [41], environment [42], hotel industry [43], airlines [44] and banking [45], [35].…”
Section: Supply Chain Performance Measurementmentioning
confidence: 99%